Breastfeeding Versus Bottle Feeding on Malocclusion in Children: A Meta-Analysis Study. (November 2018) - Thomaz, Erika Barbara Abreu Fonseca; Alves, Cláudia Maria Coelho; Gomes e Silva, Luciana Freitas; Ribeiro de Almeida, Cecília Cláudia Costa; Soares de Britto e Alves, Maria Teresa Seabra; Hilgert, Juliana Balbinot; Wendland, Eliana M.
Background: Breastfeeding plays an important role in child health. However, there are doubts about its influence on malocclusions. Systematic reviews have yielded contradictory results. Research aim: This study aimed to investigate whether the type and duration of breastfeeding are associated with malocclusions in primary teething. Methods: The review strategy included several electronic databases, lists of references, reviews, dissertation and thesis websites, experts, and other relevant documents. Published and unpublished observational studies ( N = 42) were reviewed using the Participants (children), Interventions (breastfeeding), Comparisons (bottle feeding), Outcomes (malocclusion), and Study design (observational) strategy, without restrictions on language or locale. Information about the authors, publication year, country of study, setting, study design, sample size, age, type and duration of exclusive and mixed breastfeeding, and malocclusions was recorded by two blinded evaluators. Quantitative meta-analysis ( N = 30) of the studies with available data was performed. Results: Breastfeeding was a protective factor against malocclusions. The odds of association increased with breastfeeding duration. Irrespective of duration, breastfeeding had a protective association with open bite. For those who were breastfed for up to 6 months, breastfeeding protected against overjet, open bite, posterior crossbite, and crowding. Breastfeeding for 12 months or longer was associated with lower odds of overjet, open bite, and posterior crossbite. Breastfeeding exclusively for 6 months was also a protective factor against malocclusions. However, studies on this subject presented low quality, statistical heterogeneity, and only unadjusted measures of association in most of the cases. Conclusion: Breastfeeding beneficially affects primary occlusion when practiced for at least 6 months.